2010
DOI: 10.1007/s11605-010-1291-y
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Lengthening in Adult Patients with Short Bowel Syndrome

Abstract: Bowel lengthening is technically feasible and effectively leads to weaning from PN in more than half of the adult patients. Lengthening procedures may be an underutilized treatment for adults with short bowel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 20 publications
1
30
0
2
Order By: Relevance
“…Yannam et al 171 reported the results of intestinal lengthening procedures in adult patients, including 6 Bianchi and 15 STEP procedures: PN independence was achieved in 59% and a further 18% demonstrated improved enteral caloric intake.…”
Section: Autologous Gastrointestinal Reconstructionmentioning
confidence: 99%
“…Yannam et al 171 reported the results of intestinal lengthening procedures in adult patients, including 6 Bianchi and 15 STEP procedures: PN independence was achieved in 59% and a further 18% demonstrated improved enteral caloric intake.…”
Section: Autologous Gastrointestinal Reconstructionmentioning
confidence: 99%
“…Evaluaciones recientes comunican resultados satisfactorios, tanto que algunos autores consideran que es una técnica subutilizada. En una serie de 14 adultos con una mediana de ID remanente de 45 cm, se logró un porcentaje medio de incremento de la longitud intestinal de 52% 23,24 . Según estas observaciones sería prudente considerarla como indicada en pacientes que tengan menos de 100 cms de ID remanente y ausencia o segmento muy cortos de colon.…”
Section: Discussionunclassified
“…Nevertheless, there is need to improve the long-term results, probably through improved patient selection, evolution of the graft type toward multivisceral transplantation, and new modalities of immuno-suppressive therapy. For patients who do not meet the selection criteria for intestinal transplantation, other surgical alternatives exist (intestinal lengthening and segmental reversal of the small bowel) with interesting results with regard to the ability to wean from PN and for patient survival [16,34].…”
Section: Discussionmentioning
confidence: 99%